MOLECULAR CHARACTERIZATION OF MYCOBACTERIUM AVIUM SUBSP. PARATUBERCULOSIS ISOLATES - SOBHA RANI M; PRABHAKAR TG; SAMUEL MASILMONI RONALD B (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Johne’s disease, caused by Mycobacterium avium subsp. paratuberculosis (MAP), is highly prevalent in domestic ruminants. In India, the exact prevalence of MAP genotypes still remains unknown limited, and the systematic disease control programs are also limited. This study was undertaken to study the molecular characterization of MAP isolates. Methods: About 22 MAP isolates were from cattle, sheep, and goat under gone the molecular characterization by three different methods (1) IS1311 polymerase chain reaction (PCR) with restriction enzyme analysis (REA), (2) GyrA and GyrB PCR with sequencing, and (3) digital microfluidic chip (DMC)-PCR. The study demonstrated that a) IS1311 PCR with REA (based on point mutations) identified all 22 MAP isolates as intermediate typeâ€ irrespective of a host of origin and also belong to Indian Bison type. Molecular typing based on the gyrA and gyrB genes partial amplification and sequencing revealed that the MAP isolates exhibited more lineages toward the reference Type III, Intermediate strain. Results: The MAP isolate of sheep origin showed more lineages toward the sheep type than the isolates of cattle and goats. This variation may be due to host-pathogen interactions and adaptation to different hosts and environmental conditions in the nature. Conclusions: The DMC-PCR, which is based on sequence difference at 5` end of IS900 of MAP, differentiated rapidly all the isolates as sheep type. The application of DMC-PCR to differentiate sheep and Intermediate types is limited as the Intermediate type (Type III) and sheep type (Type I) are very closely related to each other and all the MAP isolates were confirmed as Intermediate or Type III by three different methods which are commonly present in India, Spain, and Iceland. Â Â